CHILDREN'S ECZEMA AND RECOMMENDATIONS FOR ITS TREATMENT (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Eczema is a very common skin problem. The most common form of eczema is called atopic dermatitis. Atopic dermatitis often begins in infancy, affecting about 15 to 20% of children. It usually improves as the child grows older and may resolve by school age or puberty. Some children with atopic dermatitis may have more chronic disease. Complex therapy is used to treat eczema and is selected individually by the doctor for each patient.